A Case of Progressive Ossifying Fibrodysplasia of Tracheobronchial Respiratory Muscles. (11th February 2019) - Habib, Nouraly; Konan, Anhum; Bi Zamble Olivier Didier, Tra
Abstract : The authors report a case of progressive ossifying myositis (POM) in a 13-year-old boy, revealed by dry cough and dyspnea. Conventional chest x-rays and whole-body CT showed extraskeletal ossification that seems to affect the left bronchial strain and trachea. This lesional topography, if established, not yet described to our knowledge, contrasts with the observations of all the authors, including Munchmeyer, for whom smooth muscles and muscles attached to the skeleton by a single end are spared by the heterotopic ossifications characteristic of the disease. Therefore, this observation raises the question of the ubiquity of muscle ossifications during POM.